John Berkeley James (John) Wells (1935–2018)––Life, career and remembrances - Coull, Bruce C.; Bradford-Grieve, Janet M.; Hicks, Geoffrey R.f. (Zootaxa, 2021)
John Wells, who died at age 83 on 12 November 2018, was a research scientist, teacher, Professor of Zoology, Dean of Science at Victoria University of Wellington, New Zealand, family man and community leader. He was a man of his time, surviving World War II, progressing to a career that stretched around the world.